Crystallography and crystal defects - Kelly, A. (Anthony); Knowles, Kevin M. (John Wiley & Sons, 2020)
"Fully updated and expanded, this new edition of a classic text presents a unified approach to crystallography and to the defects found within crystals. The third edition of Crystallography and Crystal Defects maintains the principal objective of previous editions; to communicate the modern concepts of crystallography in a clear, succinct, manner and to put these concepts into use in the description of line and planar defects in crystalline materials, quasicrystals and crystal interfaces. The existing chapter on crystal interfaces has been divided into two new chapters, one on surfaces and grain boundaries, which will include more detail on atomistic modelling of grain boundaries, and one on interphase boundaries. Additional crystallography is included to enable readers to understand more advanced concepts such as crystallographic aspects of precipitates in matrices, while still being at a level of readership of advanced undergraduate / graduate"--